Peningkatan Minat Belajar IPAS Melalui Pemanfaatan Chromebook Berbantuan Google Workspace For Education bagi Siswa Kelas V SDN 03 Madiun Lor Kota Madiun - Gunawan, Mahfur; Hanif, Muhammad; Rifa’i, Muhammad (Universitas PGRI Madiun, 2024)
This research aims to determine whether or not it is possible to increase interest in learning social and science in fifth grade students at SDN 03 Madiun Lor through the use of chromebooks assisted by Google Workspace for Education. The approach used is a qualitative approach with the Classroom Action Research method. The research was carried out at SDN 03 Madiun Lor with 27 students of fifth grade as research subjects. Data collection techniques through observation and questionnaires. The data analysis used is qualitative and quantitative descriptive analysis. The research results show an increase in interest in learning social and science in the students after implementing chromebooks assisted by Google Workspace for Education. The learning process is more interesting and in accordance with students' learning needs and interests, as evidenced by significant increases in aspects: students' attention in learning participation; pleasure in learning activities; interest in the material presented; and participation in learning activities.